Analisis Mengelola Hutang dalam Persepektif Islam - Anita Mar’atus Zhulaiha (An Nahdhoh Jurnal Kajian Islam Aswaja, 2022)
This study aims to find out the law of debt management analysis in an Islamic perspective, both from the opinions of classical and contemporary scholars. The problem faced is accounts payable, debt is muamalah that brings a person to heaven because of the intention to help each other to help fellow human beings (hablum minannas), but can bring someone to hell if not managed properly. Therefore qordh (debt) must be managed with an Islamic perspective to get to the right path by improving the Islamic instructions contained in the Qur'an and hadith so that accounts receivable can bring blessings and create solutions for Muslims